2018
DOI: 10.1111/1759-7714.12906
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib as first‐line treatment for advanced lung adenocarcinoma patients harboring HER2 mutation: A case report and review of the literature

Abstract: HER2 mutations are a rare group of driving genes that respond to HER2 targeted therapy, particularly afatinib. No more than 20 such cases have been reported, but afatinib was used after first‐line chemotherapy. We present the case of a never‐smoking female patient diagnosed with stage IV lung adenocarcinoma harboring a Her2 exon 20 inserted mutation who achieved a durable response (12 months) to first‐line afatinib treatment. We review the literature concerning afatinib therapy in this rare cohort of mutated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This might indicate that ERBB2 mutation was a poor prognostic factor. Although the previous case report showed that ERBB2 mutated NSCLC patient could benefit from afatinib treatment, a retrospective study in China suggested that compared with chemotherapy, afatinib was not more beneficial to ERBB2 mutated NSCLC patients . Also, most of the clinical trials, including afatinib, dacomitinib, and neratinib, focused on ERBB2 exon 20 insertion mutations and failed with a low objective response rate of 11%–19% .…”
Section: Discussionmentioning
confidence: 97%
“…This might indicate that ERBB2 mutation was a poor prognostic factor. Although the previous case report showed that ERBB2 mutated NSCLC patient could benefit from afatinib treatment, a retrospective study in China suggested that compared with chemotherapy, afatinib was not more beneficial to ERBB2 mutated NSCLC patients . Also, most of the clinical trials, including afatinib, dacomitinib, and neratinib, focused on ERBB2 exon 20 insertion mutations and failed with a low objective response rate of 11%–19% .…”
Section: Discussionmentioning
confidence: 97%
“…All four responders harbored an exon 20 insertion and they were treated with Trastuzumab, Afatinib or TDM-1 (Chuang, et al, 2017). In a recent case report, a patient with the recurrent YVMA insertion treated with Afatinib first-line achieved a PR that lasted 12 months (Shi & Wang, 2018). Another group reported the case of a woman with NSCLC harboring a HER2 exon 20 mutation (c.2437A>G) who previously failed cytotoxic chemotherapy and Gefitinib treatment but responded to Afatinib .…”
Section: Clinical Responses In Her2 Mutant Lung Cancer Patients To Anmentioning
confidence: 99%
“…The first case is an account of a never-smoking female with a HER2 V659E mutation who had a confirmed PR for 5 months, and the second case described a female never-smoker with a HER2 pG776delinsVC who achieved a PR for 12þ months. 6,7 No other TKIs have been evaluated in the first-line setting. In a basket trial of ado-trastuzumab, 2 of 3 untreated patients enrolled achieved a PR.…”
Section: Discussionmentioning
confidence: 99%